Hadis Kuraib Dalam Konsep Rukyatul Hilal - Muslih Husein (Jurnal Penelitian, 2016)
Hisab and rukyat is a way to know the turn of the month. This study shows several findings. First is the correlation between Kuraib traditions and differences in the determination of the beginning of Ramadan, Shawwal, and Dhul-Hijjah in Indonesia. Ministry of Religious Affairs of the Republic of Indonesia has stated that Indonesia as a whole into a single jurisdiction (wilayatul hukmi). Second, on the success rukyat al-hilal in one area that applied to other regions of earth. Important to know that the first visibility of the new moon does not cover the entire face of the earth on the same day, but splitting it into two parts: (1) part of the West to see the new moon, and (2) part of the East were not able to see the new moon.